The Effect of Gaze and Product Salience on Digital Visual Engagement: An Experimental Research - Andreas, Jonathan Alpha; Irawan, Kenny; Rahman, Fathony (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2022)
This study investigates the effects of gaze and product salience in visual content, which can build engagement on social media. The variables used were visual social semiotics, digital visual engagement, attitude, and the purchase intention. Two hundred participants were recruited using Amazon Mechanical Turk. To see the interaction between gaze and product salience, a 2x2 experimental design was used. Regression was used to see the relationship between digital visual engagement with attitude and purchase intention. This study offers empirical evidence that there is an interaction between gaze and product salience on digital visual engagement, with a positive effect on digital visual engagement from the direct gaze and high product salience condition. Furthermore, this study found a relationship between digital visual engagement with attitude and purchase intention. The results show that digital visual engagement positively influences attitude and purchase intention. This hypothesis is tested on a single product category. Further studies might replicate this experiment with other products, visual content, online platforms, and factors based on visual social semiotics theory. This study offers managers knowledge on making visual content that will produce more engagement, especially in social media ads, which can influence the attitude and purchase intention of their audience.